Evaluation of the Potential of five Housekeeping Genes for Identification of Quarantine Pseudomonas syringae. Issue 2 (February 2017) - Lu, Songyu; Tian, Qian; Zhao, Wenjun; Hu, Baishi
Abstract: The Pseudomonas syringae species, containing approximately 60 pathovars, causes bacterial plant diseases on numerous crops and results in great economic losses. It is difficult to rapidly and accurately identify and detect P. syringae due to its complicated classification system. It has also been shown that housekeeping genes have great potential in phylogenetic analysis and classification of bacteria. In this study, phylogenetic analyses of five housekeeping genes, including 16S rRNA, rpoD, gapA, gltA and gyrB, were performed for 100 Pseudomonas strains. Our results showed that two housekeeping genes ( rpoD and gapA ) had the maximum ability in distinguishing the majority of Pseudomonas pathovars, whereas rpoD exhibited the best for precise and efficient detection of five P. syringae strains, which is of quarantine significance to China.